A Bibliometric Exploration of Facebook Marketing Research Trends Using Scopus Database - Buamonabot, Irfandi; Susilo, Daniel; Thanos, Guellica Agnesia Claudia; Sam, Toong Hai; Timotius, Elkana; Tammubua, Milcha Handayani; Rudiansyah, R. (Journal of Applied Science, Engineering, Technology, and Education, 2024)
Facebook has developed into much more than just a social media platform since its 2004 launch, changing the way businesses engage with their customers and emerging as a powerful player in the field of digital marketing. Due to the increased attention this evolution has received from academia, extensive research has been conducted on a number of Facebook marketing-related topics, such as customer engagement, brand building, and consumer data collection. Using Scopus as a data source, we conducted a bibliometric analysis in this study to thoroughly review the literature on Facebook marketing and identify important trends, hotspots, and areas in need of further research. 133 pertinent publications from 2009 to 2023 were found by our analysis, underscoring Facebook's significance in digital marketing. This study sheds light on several Facebook marketing research themes, including the efficacy of advertising, consumer behavior on social networks, ethics, and privacy. Furthermore, we found that research is scattered worldwide indicating differences in digital marketing connected to society, economy, and culture. Topics such artificial intelligence, cross-cultural marketing, and the consequences of Facebook algorithm modifications still have more to be discovered even with the wealth of studies. This study supports the relevance of Facebook in digital marketing, indicates areas that demand more research for a better knowledge of the successful use of Facebook in marketing strategies, and provides insight for academics and practitioners.